2023
DOI: 10.1186/s12943-023-01723-z
|View full text |Cite
|
Sign up to set email alerts
|

CAR-cell therapy in the era of solid tumor treatment: current challenges and emerging therapeutic advances

Abstract: In the last decade, Chimeric Antigen Receptor (CAR)-T cell therapy has emerged as a promising immunotherapeutic approach to fight cancers. This approach consists of genetically engineered immune cells expressing a surface receptor, called CAR, that specifically targets antigens expressed on the surface of tumor cells. In hematological malignancies like leukemias, myeloma, and non-Hodgkin B-cell lymphomas, adoptive CAR-T cell therapy has shown efficacy in treating chemotherapy refractory patients. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 277 publications
0
110
0
Order By: Relevance
“…Contrary to CD3‐PPP/pCAR@α‐CD supramolecular hydrogel‐treated ones, the proportion of native CAR‐T cells in solid tumors was low, while the proportion study showed a significant decline with the extension of treatment time in the blood and tumor tissues, in terms of mice treated with intravenous infusion of CAR‐T cells, which is consistent with previous report. [ 17 ] These results can be attributed to two factors: 1) CD3‐PPP/pCAR@α‐CD provides a “factory” for cell generation, wherein the nanocomplexes released by the slow degradation of hydrogel continually in situ produced CAR‐T cells, while these CAR‐T cells could directly enrich in solid tumor rather than supplying bolus administration like intravascular infusion. 2) CD3‐PPP/pCAR@α‐CD‐generated CAR‐T cells bypassed in vitro expansion, while the enhanced production of these self‐renewing T cell populations might further contribute to increased cellular persistence.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to CD3‐PPP/pCAR@α‐CD supramolecular hydrogel‐treated ones, the proportion of native CAR‐T cells in solid tumors was low, while the proportion study showed a significant decline with the extension of treatment time in the blood and tumor tissues, in terms of mice treated with intravenous infusion of CAR‐T cells, which is consistent with previous report. [ 17 ] These results can be attributed to two factors: 1) CD3‐PPP/pCAR@α‐CD provides a “factory” for cell generation, wherein the nanocomplexes released by the slow degradation of hydrogel continually in situ produced CAR‐T cells, while these CAR‐T cells could directly enrich in solid tumor rather than supplying bolus administration like intravascular infusion. 2) CD3‐PPP/pCAR@α‐CD‐generated CAR‐T cells bypassed in vitro expansion, while the enhanced production of these self‐renewing T cell populations might further contribute to increased cellular persistence.…”
Section: Discussionmentioning
confidence: 99%
“…The mononuclear phagocyte system (MPS) consists mainly of monocytes and monocyte-derived macrophages. They both have phagocytic functions [139]. Phagocytes are highly plastic cells.…”
Section: Macrophagesmentioning
confidence: 99%
“…Additionally, CAR-M that were administered intravenously (IV) were found to localize to tumors in several xenograft models and persisted in tumor-free mice (primarily within the liver) for at least 62 days, as detected by whole-body bioluminescent imaging. In vitro analysis further demonstrated that CAR-M were capable of coordinating an antitumor T cell response by recruiting T cells and cross-presenting antigens from phagocytosed cells [19,86,87].…”
Section: Car-macrophagesmentioning
confidence: 99%